1984
DOI: 10.1038/308814a0
|View full text |Cite
|
Sign up to set email alerts
|

Transduction and rearrangement of the myc gene by feline leukaemia virus in naturally occurring T-cell leukaemias

Abstract: Evidence of myc gene transduction by feline leukaemia virus in several spontaneous lymphoid tumours of cats suggests that recombinant viruses carrying oncogenes may be much more involved in oncogenesis in natural conditions than previously recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
0
3

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(96 citation statements)
references
References 31 publications
2
91
0
3
Order By: Relevance
“…The disrupted chicken c-myc locus is often transcribed from a viral promoter present in the long terminal repeat (18,21,32) and sometimes from cryptic promoters (25,32). Murine thymomas caused by murine leukemia viruses as well as feline T-cell tumors caused by feline leukemia virus also frequently contain a disrupted c-myc locus (10,23,24,29,39). Chicken and feline c-myc genes are both progenitors of v-myc oncogenes contained in several replication-defective viruses and causing rapid onset of myelomonocytic tumors and carcinomas in chickens (1, 46) and lymphoid tumors in cats (23,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The disrupted chicken c-myc locus is often transcribed from a viral promoter present in the long terminal repeat (18,21,32) and sometimes from cryptic promoters (25,32). Murine thymomas caused by murine leukemia viruses as well as feline T-cell tumors caused by feline leukemia virus also frequently contain a disrupted c-myc locus (10,23,24,29,39). Chicken and feline c-myc genes are both progenitors of v-myc oncogenes contained in several replication-defective viruses and causing rapid onset of myelomonocytic tumors and carcinomas in chickens (1, 46) and lymphoid tumors in cats (23,29).…”
mentioning
confidence: 99%
“…Murine thymomas caused by murine leukemia viruses as well as feline T-cell tumors caused by feline leukemia virus also frequently contain a disrupted c-myc locus (10,23,24,29,39). Chicken and feline c-myc genes are both progenitors of v-myc oncogenes contained in several replication-defective viruses and causing rapid onset of myelomonocytic tumors and carcinomas in chickens (1, 46) and lymphoid tumors in cats (23,29). Although the function of the myc protein is speculative, the protein binds DNA in vitro (13,33), is associated with the nucleus in vivo (2,13,16,33), and may play a central role in the control of cell growth (8,22).…”
mentioning
confidence: 99%
“…Although the steadystate levels of c-myc protein in exponentially growing cells are constant during the cell cycle {Hann et al 1985; Rabbitts et al 1985; Thompson et al 1985), decreased levels achieved by antisense c-myc oligonucleotides (Heikkila et al 1987) or by genetic disruption of one c-myc gene copy (Shichiri et al 1993) have been reported to interfere with cell growth, indicating that c-myc is required for cell-cycle progression. Moreover, constitutive overexpression of c-myc in some cell types reduces their growth factor requirement in vitro (Kaczmarek et al 1985) and predisposes to tumor formation in several experimental animal models (Corcoran et al 1984;Li et al 1984;Neil et al 1984;Selten et al 1984;Stewart et al 1984;Adams et al 1985;Leder et al 1986; Spanopoulou 6Corresponding author. et al 1989).…”
mentioning
confidence: 99%
“…Similarly, erbB is specifically associated with erythroblastosis in chickens but with squamous cell carcinoma and other epithelial tumors in humans (3,10,14). By contrast, many more parallels exist with the myc oncogene whose activation has been linked to B-and T-cell disorders in a variety of species, including chicken, mouse, rat, cat, and human (2,9,16,25,29,34,37; reviewed in reference 30). It therefore remains an entirely open question whether int-2 will eventually be implicated in human tumors other than mammary carcinomas, and the negative findings to date in no way preclude further investigation along these lines.…”
Section: Discussionmentioning
confidence: 99%